The Importance of Mother Tongue to the Cultivation of Values and Personality Development: A Philosophical Aspect - Kardelis, Naglis (Vilnius University Open Series, 2020)
The author of the article examines the relation between language and values from the perspective of a native speaker who finds in his or her mother tongue a linguistic articulation of those values that are prevalent in the speaker’s community and are shared by all or most of its members. Language is a unique medium where values are presented, examined and constantly re-evaluated by members of a linguistic community. Especially the native speaker’s mother language, much better than any other language learned later in life, reveals its special role in the process of a person’s moral growth and overall personal development. The mother tongue shared by certain linguistic community plays the leading role in forming one’s world view, and this linguistically created world outlook is imbued with specific moral and aesthetic values characteristic of that linguistic community. The mother language not only emerges as a bridge that connects the native speaker to his or her ancestors and the entire cultural legacy created by former generations, but also reveals itself as the most rewarding medium for the expression of the native speaker’s personal experience and personal creative insights. The author of the article is of the opinion that the appreciation of one’s mother tongue and the recognition of its privileged status should not be viewed as leading to linguistic and cultural isolation, but as opening the gate to other languages and linguistic world views. What is even more important is that, in the author’s opinion, the appreciation of one’s mother tongue enhances one’s ability to appreciate the linguistic medium as such and to celebrate language as such, not only one’s mother language. Respect for our mother tongue also enhances our capacity to creatively and respectfully encounter other languages and other linguistically construed world views. Yet it is also argued that we should not view our mother tongue as the only, albeit very authoritative, guide in the sphere of values – our own critical mind and critical reflexion on the nature of values should go hand in hand with the received collective wisdom that we find crystalized in our mother tongue, in language as such, as well as in all forms of traditional culture.